Anatomy of frauds. Types, conditions, prevention measures - Mackevičius, Jonas; Ragauskiene, Erika (Anatomia oszustw. Rodzaje, uwarunkowania, środki zapobiegawcze, 2011)
Frauds are committed in all the areas of human activities, in all countries – only their scope, methods, and motives differ. In the current dynamic and competitive business environment, they are committed using the latest scientific achievements and advanced technologies. Frauds always make the major financial scandals and bankruptcies of world’s biggest companies. The article explores the main fraud types: misappropriation of assets, corruption, tax evasion, distortions of financial statements, etc. It suggests fraud diagnostics and prevention measures
Ekonomia = Economics, 2011, Nr 2 (14), s. 204-213
Keywords: frauds; types; prevention